Chromatographic purification of virus particles for advanced therapy medicinal products - Mendes, João Pedro Pereira (2017)
The increasing number of cancer diagnoses in the last decades is associated with behavioral risks, in addition with those genetically originated. The fight against the disease usually relapses in not selective mechanisms like chemotherapy or radiotherapy, that induce the organism in deep alterations and side effects. One of the alternative strategies relies on the use of advanced therapies medicinal products suchlike viruses, to carry out the treatment in each cell taking advantage of their invading abilities. The cost of producing this oncolytic virus directly influences process engineering, and thus, numerous efforts have been made to improve each purification step. The development of the downstream process begins with the clarification of the viruses harvested from the bioreactor with two depth-filtration steps. This allows a gradual removal of larger impurities like cell debris with a complete virus recovery. Afterwards, a tangential flow filtration step enables volume reduction. After concentration, the retentate is subjected to diafiltration which allows not only the permeation of impurities but also the formulation of the concentrated product for the next processing step. The following step in the purification train is anion exchange chromatography. The chromatographic media used was selected after successive screening tests with a library of resins and membranes. The conditions used reflect the study carried out, in the sense that the load employed corresponds to the DBC10% obtained of 6.2 x 1011 (TP/ml) particles per millilitre and the elution of the viruses is preceded by a low salt concentration elution (200 mM) in order to remove impurities. The yield obtained is 85%. The purification process ends with polishing and sterile filtration to achieve the specified conditions, through a size-exclusion chromatography and membrane filters, respectively, obtaining a total yield of 53%. The study also opens perspectives on innovation and future development with the performance of multi-column chromatography assays and automated filtration tests, both in specialized equipment.